Pengaruh PDRB Per Kapita, IPM dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan di Nusa Tenggara Barat (2020-2022) - Karimah, Fadhillah; Harsono, Iwan; Endang Astuti; Himawan Sutanto; Ida Ayu Putri Suprapti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Poverty is a problem in a complex and multidimensional economy. Therefore, solutions are needed to overcome and reduce poverty levels. This research aims to analyze the influence of the independent variables Gross Regional Domestic Product (GRDP), unemployment rate, Human Development Index (HDI) on the amount of poverty in West Nusa Tenggara Province in 2020-2022. Data was obtained from the West Nusa Tenggara Province Central Statistics Agency, namely in various prints of West Nusa Tenggara Province in Figures, Data and Information on West Nusa Tenggara Poverty Issues 2020-2022. .The analysis tool used is panel data regression. In this research, the model used is Fixed Effects, because the Fixed Effects model is better than other models, which have been tested using the F test and the Hausman test. The results show that the Gross Regional Domestic Product (GRDP) variable, the Human Development Index (HDI), has a negative and significant effect on the amount of poverty in West Nusa Tenggara, while the Regency/City unemployment rate variable has a significant positive effect on the amount of poverty in West Nusa Tenggara.